2008
DOI: 10.1016/j.bbr.2008.04.020
|View full text |Cite
|
Sign up to set email alerts
|

A combined [11C]diprenorphine PET study and fMRI study of acupuncture analgesia

Abstract: Functional neuroimaging studies suggest that a lateral network in the brain is associated with the sensory aspects of pain perception while a medial network is associated with affective aspects. The highest concentration of opioid receptors is in the medial network. There is significant evidence that endogenous opioids are central to the experience of pain and analgesia. We applied an integrative multimodal imaging approach during acupuncture. We found functional magnetic resonance imaging signal changes in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 46 publications
3
77
0
Order By: Relevance
“…The four studies which compared verum acupuncture with the Streitberger Needle were all from the US and showed heterogeneous results [16,19,21,22]. Yoo et al [16] found more activation associated with verum acupuncture in the somatosensory areas and motor areas.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The four studies which compared verum acupuncture with the Streitberger Needle were all from the US and showed heterogeneous results [16,19,21,22]. Yoo et al [16] found more activation associated with verum acupuncture in the somatosensory areas and motor areas.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Here, we will focus on the regions most commonly associated with Neuroticism and Extraversion across studies: the insular cortex, OFC, amygdala, and ventral striatum. The literature suggests there is a substantial density of opioid receptors in all four of these regions, which enables us to detect whether opioid receptor binding potential, a proxy of baseline opioid function, is correlated with Neuroticism and Extraversion [31,32]. We hypothesized that opioid receptor binding potential in these regions would vary as a function of Neuroticism and Extraversion.…”
Section: Introductionmentioning
confidence: 99%
“…It is becoming more common to acquire multimodality neuroimaging data that include PET and fMRI, as well as other types of MR (and optical) outcomes (Apkarian et al, 2005;Catana et al, 2008;Dougherty et al, 2008;Herzog et al, 2011;Huppert et al, 2008;Newberg et al, 2005;Rabiner et al, 2011;Sperling et al, 2009;Tong et al, 2011). Combined fMRI and PET brain imaging will become even more commonplace with the increased availability of combined PET/MR imaging systems.…”
Section: Multimodality Imagingmentioning
confidence: 99%